Ethics in Law Enforcement - McCartney, Steve; Parent, Rick; Open Textbook Library (Open Textbook Library, 2015)
In this book, you will examine the moral and ethical issues that exist within law enforcement. This book will also familiarize you with the basic history, principles, and theories of ethics. These concepts will then be applied to the major components of the criminal justice system: policing, the courts, and corrections. Discussion will focus on personal values, individual responsibility, decision making, discretion, and the structure of accountability. Specific topics covered will include core values, codes of conduct, ethical dilemmas, organizational consequences, liability, and the importance of critical thinking. By the end of this book, you will be able to distinguish and critically debate contemporary ethical issues in law enforcement.
Chapter 1: Ethical Behaviour -- 1.1 The Importance of Ethical Behaviour -- 1.2 Ethics and the Pursuit of a Law Enforcement Career -- 1.3 As Employees in Law Enforcement Agencies -- Chapter 2: Ethical Systems -- 2.1 Major Ethical Systems -- 2.2 Utilitarian Ethics -- 2.3 Deontology -- 2.4 Virtue Ethics -- 2.5 Ethics of Care -- 2.6 Egoism -- 2.7 Religion or Divine Command Theory -- 2.8 Natural Law -- 2.9 Social Contract Theory -- 2.10 Rawls' Theory of Justice -- 2.11 Moral Relativism -- Chapter 3: Ethical Dilemmas and the Process of Effective Resolution -- 3.1 Ethical Dilemmas -- 3.2 Values -- 3.3 Solving Ethical Dilemmas -- Chapter 4: Key Ethical Issues within Law Enforcement -- 4.1 Ethical Issues -- 4.2 The Ethics of Power and Authority -- 4.3 The Milgram Experiment -- 4.4 Person, Gender, and Cultural Differences in Conformity -- 4.5 Ethical Issues during an Investigation -- 4.6 Gratuities -- Chapter 5: Accountability and Investigation -- 5.1 Autonomy and Accountability -- 5.2 British Columbia's Police Act -- 5.3 The Royal Canadian Mounted Police Act -- 5.4 Investigation Models -- 5.5 Independent Investigations Office -- Chapter 6: Policing -- 6.1 Noble Cause Corruption -- 6.2 Policing Public Demonstrations and Crowd Control -- 6.3 Sex Offender Notification Laws -- 6.4 Ethics of Private Policing -- Chapter 7: Discretion, Supervision, and Leadership -- 7.1 The Ethics Surrounding Discretion -- 7.2 Discretion and Supervision -- 7.3 Selective Enforcement -- 7.4 Loyalty -- 7.5 Ethical Leadership -- 7.6 Transactional and Transformational Leadership -- Chapter 8: The Culture of Law Enforcement -- 8.1 Police Subculture -- 8.2 Socialization of Police -- 8.3 Skepticism and Cynicism -- 8.4 Moral Culpability versus Legal Culpability
In English.
Description based on print resource
Keywords: Law -- Textbooks -- United States